Are people with an intellectual disability at increased risk of attachment difficulties? A critical review. (March 2021) - Hamadi, Layla; Fletcher, Helen K
Attachment difficulties are associated with a range of adverse outcomes in mental health, and people with intellectual disabilities (IDs) may be at greater risk of experiencing difficulties in their attachment relationships. This review critically evaluated recent research measuring the prevalence of attachment difficulties in people with ID. Eight studies met the inclusion criteria, and a higher prevalence of insecure and disorganized attachment classifications, and symptoms of attachment disorder, was found across a number of subgroups of people with diagnoses of ID. However, the validity and reliability of measures of attachment have not been empirically established in this population, and control groups were not always appropriate. These findings indicate the need to (1) develop reliable and standardized assessments of attachment for people with ID and (2) evaluate the efficacy of attachment-based interventions in relation to reducing psychological distress, mental health problems and expression of behaviours experienced by others as challenging.